2013
DOI: 10.1186/1746-4811-9-43
|View full text |Cite
|
Sign up to set email alerts
|

Validation of doubled haploid plants by enzymatic mismatch cleavage

Abstract: BackgroundDoubled haploidy is a fundamental tool in plant breeding as it provides the fastest way to generate populations of meiotic recombinants in a genetically fixed state. A wide range of methods has been developed to produce doubled haploid (DH) plants and recent advances promise efficient DH production in otherwise recalcitrant species. Since the cellular origin of the plants produced is not always certain, rapid screening techniques are needed to validate that the produced individuals are indeed homozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
0
19
0
3
Order By: Relevance
“…Mixtures of genomic DNA from a DH plant and GP show cleavage products, while mixture of the same material with HOR1606 does not, indicating the DH harbours the HOR1606 allele (lanes 14 and 15). This figure and legend are reproduced from (Hofinger et al 2013) similar results, use the cheaper version. Some Taq polymerases, like TaKaRa Ex Taq, come supplied with dNTPs and buffer containing MgCl 2 .…”
Section: Agarose Gel Electrophoresis and Data Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…Mixtures of genomic DNA from a DH plant and GP show cleavage products, while mixture of the same material with HOR1606 does not, indicating the DH harbours the HOR1606 allele (lanes 14 and 15). This figure and legend are reproduced from (Hofinger et al 2013) similar results, use the cheaper version. Some Taq polymerases, like TaKaRa Ex Taq, come supplied with dNTPs and buffer containing MgCl 2 .…”
Section: Agarose Gel Electrophoresis and Data Analysismentioning
confidence: 97%
“…As a proof of principle, Hofinger et al (2013) developed this method for barley and compared it to another approach for validation of DH plants: simple sequence repeat (SSR) markers (Hofinger et al 2013). In this work, the authors showed that 11/26 primer pairs were suitable for DH validation by enzymatic mismatch cleavage, while only 3/32 previously characterized SSR primer sets were suitable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8.6 Mismatch cleavage with crude enzyme extracts containing single-strand-specific nucleases prepared from weedy plants (W) or celery (C). PCR products of the target gene nb2-rdg2a (1,500-bp-PCR product) were produced from genomic DNA of barley containing a known SNP (Hofinger et al 2013). The PCR products were digested with weed and celery enzyme extracts at different concentrations (listed above sample).…”
Section: Discussionmentioning
confidence: 99%
“…8.4 PCR amplification of genomic DNAs described in Chap. 7 using primers for the barley nb2-rdg2a (top panel) and nbs3-rdg2a (bottom panel) gene targets as described in Hofinger et al (2013). Samples are loaded in the same order as in Fig.…”
Section: Example Of Pcr Products Using Tilling Primers With Source Gementioning
confidence: 99%